Blockchain and Freedom to Conduct a Business: Between Myth and Reality - Della Pietra, Attilio (The Age of Human Rights Journal, 2023)
Recent advances in technology have demonstrated the enormous flexibility of Distributed Ledger Technology (DLT), whose potential goes well beyond the cryptocurrency trading. This article explores the potential impact that the utilization of a permissioned blockchain could have on listed companies and how this could be an appropriate instrument for a more effective implementation of the provisions of the Shareholder Rights Directive II. This technological infrastructure could attest the correct formation of will within the shareholders’ meeting and contribute to the creation of a truly democratic space for the meeting and discussion among shareholders, thus allowing achievement of freedom to conduct a business. However, the most advanced use of blockchain technology has a disruptive effect and exposes us to the great danger of an “algocratic” drift. Therefore, this article analyses the main critical issues from both a technical and legal viewpoint of Decentralized Autonomous Organizations (DAOs).